Mechanistic insights into efficient methylene blue adsorption by single-rod mangosteen peel waste composite starch cryogel: Batch and column studies - Phatthanawiwat, Kharittha; Phawachalotorn, Chanadda; Wongniramaikul, Worawit; Choodum, Aree (My University, 2026)
A green composite tablet, based on the immobilization of mangosteen peel (MP) waste particles in starch cryogel (Cry-DMP), was successfully prepared and characterized. Cry-DMP exhibited a high adsorption capacity for methylene blue (MB), with a maximum capacity (qₘₐₓ) of 26.53 mg g⁻¹ , and the equilibrium data were best described by the Langmuir model ( R² = 0.9902). High removal efficiencies of 97.21 % in synthetic water and 70.8 % in real Batik industrial wastewater were achieved without chemical activation of the mangosteen peel particles, demonstrating the practical applicability of the adsorbent. The suggested adsorption mechanism mainly relies on electrostatic interaction with additional contributions from hydrogen bonding and π–π interactions. The pseudo-second-order model best described the adsorption kinetics ( R² = 1), and the adsorption of MB onto Cry-DMP was determined to be spontaneous and endothermic. Furthermore, the Yoon–Nelson model accurately described the experimental results from continuous flow experiments ( R 2 = 0.8598–0.9981). Sodium silicate reduces removal efficiency by 8.82 %, while sodium phosphate increases it by 2.94 %. Cry-DMP effectively removes MB and other cationic dyes but is ineffective against anionic dyes, highlighting its selective adsorption capabilities. These findings emphasize the effectiveness of Cry-DMP as a green adsorbent for MB and highlight the feasibility of waste utilization with a greener approach.
Keywords: Batch adsorption; Biomass utilization; Continuous flow adsorption; Mangosteen peel; Methylene blue; Starch cryogel